Modernizing the tradition: Mengaji among children of urban Muslim families in Indonesia - Alviani Rachma (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
Muslims believe that the Qur’an is the main source of Islamic values, and teaching it to children early is important. The tradition of mengaji, or learning the Qur’an, has been impacted by globalization and modernization. Still, new methods such as online learning and fun-learning techniques have emerged to make the tradition more innovative and creative for children. This article discusses how modernization changes the way of learning activities in reading al-Quran for children (mengaji) in urban areas. Their tradition of going to the TPA/TPQ (Taman Pendidikan Al-Qur’an) shifted to the modern way. It taught Muslims to live alongside digital technology and an internet connection following current conditions. Following the new opportunity to learn Qur’an intensively for children, private Islamic institutions attract some urban muslim families to teach their children Qur’anic reading, such as Binar Qur’an institution. The analysis is conducted by descriptive qualitative research, which is stated by the respondents verbally and in real behavior. The data is obtained through reduction data, explaining data, and drawing a conclusion. Research shows that the impact of modernization forces people to educate their children on Qur’anic reading. It shows that the situation helps the Muslim family to be modern regarding Islamic education. Moreover, the hard struggle of parents to preserve their children in the Islamic path of society is by busying their children with positive activities such as mengaji to fulfill their growth with the Islamic nuance and to produce a better Muslim generation in the future.